Ribosomal Elongation Factor 4 Promotes Cell Death Associated with Lethal Stress - Liping Li (American Society for Microbiology, 2014)
ABSTRACT Ribosomal elongation factor 4 (EF4) is highly conserved among bacteria, mitochondria, and chloroplasts. However, the EF4-encoding gene, lepA, is nonessential and its deficiency shows no growth or fitness defect. In purified systems, EF4 back-translocates stalled, posttranslational ribosomes for efficient protein synthesis; consequently, EF4 has a protective role during moderate stress. We were surprised to find that EF4 also has a detrimental role during severe stress: deletion of lepA increased Escherichia coli survival following treatment with several antimicrobials. EF4 contributed to stress-mediated lethality through reactive oxygen species (ROS) because (i) the protective effect of a ΔlepA mutation against lethal antimicrobials was eliminated by anaerobic growth or by agents that block hydroxyl radical accumulation and (ii) the ΔlepA mutation decreased ROS levels stimulated by antimicrobial stress. Epistasis experiments showed that EF4 functions in the same genetic pathway as the MazF toxin, a stress response factor implicated in ROS-mediated cell death. The detrimental action of EF4 required transfer-messenger RNA (tmRNA, which tags truncated proteins for degradation and is known to be inhibited by EF4) and the ClpP protease. Inhibition of a protective, tmRNA/ClpP-mediated degradative activity would allow truncated proteins to indirectly perturb the respiratory chain and thereby provide a potential link between EF4 and ROS. The connection among EF4, MazF, tmRNA, and ROS expands a pathway leading from harsh stress to bacterial self-destruction. The destructive aspect of EF4 plus the protective properties described previously make EF4 a bifunctional factor in a stress response that promotes survival or death, depending on the severity of stress. IMPORTANCE Translation elongation factor 4 (EF4) is one of the most conserved proteins in nature, but it is dispensable. Lack of strong phenotypes for its genetic knockout has made EF4 an enigma. Recent biochemical work has demonstrated that mild stress may stall ribosomes and that EF4 can reposition stalled ribosomes to resume proper translation. Thus, EF4 protects cells from moderate stress. Here we report that EF4 is paradoxically harmful during severe stress, such as that caused by antimicrobial treatment. EF4 acts in a pathway that leads to excessive accumulation of reactive oxygen species (ROS), thereby participating in a bacterial self-destruction that occurs when cells cannot effectively repair stress-mediated damage. Thus, EF4 has two opposing functions—at low-to-moderate levels of stress, the protein is protective by allowing stress-paused translation to resume; at high-levels of stress, EF4 helps bacteria self-destruct. These data support the existence of a bacterial live-or-die response to stress.